Familial Clinical Heterogeneity of Medullary Thyroid Cancer with Germline RET S891A Protooncogene Mutation: 7-year Follow-up with Successful Sorafenib Treatment - Sirmen Kızılcan Çetin; Zeynep Şıklar; Elif Özsu; Ayşegül Ceran; Koray Ceyhan; Zehra Aycan; Ayça Kırmızı; Handan Dinçaslan; Emel Ünal; Merih Berberoğlu (JCRPE)
Hereditary forms of medullary thyroid carcinoma (MTC) are rare. Different phenotypes with the same mutation may be due to differences in the timing of rearranged during transfection (RET) activation steps, additional mutations in other regions of the gene, or the co-occurrence of germline and somatic mutations, which is an infrequent possibility. Here, we present the different features and challenges during the follow-up of three family members with the same germline mutation.A 4-year-old male patient with respiratory distress was diagnosed with MTC and found to have a heterozygous germline mutation C.2671T>G(S891A) in the RET gene (classified as intermediate risk by the American Thyroid Association. As the tumor was inoperable, treatment with a tyrosine kinase inhibitor (sorafenib) was initiated. This treatment with sorafenib prevented tumor progression for seven years. Whole exome sequencing did not identify additional mutations. Segregation analysis showed the same mutation in the asymptomatic mother and sister. In the proband, thyroid tissues were examined for somatic mutations, and SDHA c.1223C>T (p.S408L) was found.The clinical presentation of rare mutations such as RET p.S891A differed among family members carrying the same germline mutation. Our index case’s more severe clinical presentation may be due to an additional somatic mutation. Sorafenib treatment can be an option for advanced MTC and may prevent disease progression.